1998
DOI: 10.1002/(sici)1097-0266(199810)19:10<927::aid-smj989>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the keiretsu on the export performance of Japanese companies: help or hindrance?

Abstract: This study investigates the effect that membership in a financial keiretsu has on the export performance of Japanese manufacturing companies. Companies that belong to one of the six major financial keiretsu are found to have lower export ratios than similar companies who are not members. The negative effects of keiretsu membership appear confined to producer goods companies where intergroup linkages such as preferential trading relationships are tightest. Additional evidence from the producer goods sector show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Non-keiretsu affiliated firms are more diversified on both the international and the product dimensions than are keiretsu members. We confirm Hundley and Jacobson's (1998) finding that non-keiretsu firms show export ratios more than five percentage higher than keiretsu-affiliated firms. However, while these same firms are also consistently higher performers, only ROA, of the performance variables, shows a significant difference between the two groups.…”
Section: Comparisons Of Meanssupporting
confidence: 82%
See 3 more Smart Citations
“…Non-keiretsu affiliated firms are more diversified on both the international and the product dimensions than are keiretsu members. We confirm Hundley and Jacobson's (1998) finding that non-keiretsu firms show export ratios more than five percentage higher than keiretsu-affiliated firms. However, while these same firms are also consistently higher performers, only ROA, of the performance variables, shows a significant difference between the two groups.…”
Section: Comparisons Of Meanssupporting
confidence: 82%
“…Various authors suggest that keiretsu membership may affect product diversification strategy, as keiretsu tend to rely on group relationships to gain economies of scope and scale rather than on internal diversification or true markets. Various studies also address the issue of whether keiretsu membership affects export performance (Hundley and Jacobson, 1998). Internal sales, the existence of group trading companies, and possible negative competitive effects are discussed by Hundley and Jacobson (1998) as being related to lower export sales on the part of horizontal or financial keiretsu.…”
Section: The Effects Of Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…District membership was established when the firm was located in one of the industrial districts identified by previous research. We therefore incorporated a dummy variable to distinguish between district member and nonmember firms, similar to other previous studies (Hundley and Jacobson 1998;among others). 4 In order to reinforce the internal consistency of the objective measurement of district membership, we included a perceptual variable in the questionnaire to measure feeling of belonging.…”
Section: The Mediating Effect Of Cognitive Social Capital 69mentioning
confidence: 99%